2023
DOI: 10.3389/fendo.2023.1145914
|View full text |Cite
|
Sign up to set email alerts
|

Association of arterial stiffness with all-cause and cause-specific mortality in the diabetic population: A national cohort study

Abstract: BackgroundEstimated pulse wave velocity (ePWV) has been proposed as a potential alternative to carotid-femoral pulse wave velocity to assess the degree of aortic stiffness, and may predict cardiovascular disease (CVD) outcomes and mortality in the general population. However, whether arterial stiffness estimated by ePWV predicts all-cause and cause-specific mortality in patients with diabetes mellitus (DM) has not been reported.MethodsThis was a prospective cohort study with data from the National Health and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…In the Systolic Blood Pressure Intervention Trial, which included 9361 participants with high risk profiles, an elevated ePWV was associated with cardiovascular risk, independently of Framingham Risk scores [ 12 ]. Further studies have underscored the prognostic value of ePWV in stroke patients [ 13 ] and those with diabetes mellitus [ 21 ]. Yet, the significance of ePWV for patients undergoing a PCI has not been firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…In the Systolic Blood Pressure Intervention Trial, which included 9361 participants with high risk profiles, an elevated ePWV was associated with cardiovascular risk, independently of Framingham Risk scores [ 12 ]. Further studies have underscored the prognostic value of ePWV in stroke patients [ 13 ] and those with diabetes mellitus [ 21 ]. Yet, the significance of ePWV for patients undergoing a PCI has not been firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…We applied hypertension assessment criteria: SBP ≥ 140 mmHg or DBP ≥ 90 mmHg and the patients using anti-hypertensive medications for the period of being investigated ( 26 ). We applied diabetes evaluation criteria: doctor diagnosis as diabetes, HbA1c ≥ 6.5%, fasting glucose ≥ 7.0mmol/L, random blood glucose ≥ 11.1mmol/L, 2h OGTT blood glucose ≥ 11.1mmol/L, or being treated with diabetes drugs and insulin ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research showed that ePWV had a good consistency with both cfPWV and baPWV [ 11 ], and further investigation found that ePWV was closely related to the incidence of new-onset hypertension [ 12 ], cardiovascular events [ 13 , 14 ], all-cause [ 13 , 15 ] and specific-cause mortality [ 15 ]. However, there is still controversy over whether the association between ePWV and adverse clinical outcomes is independent of traditional cardiovascular risk estimation model or risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still controversy over whether the association between ePWV and adverse clinical outcomes is independent of traditional cardiovascular risk estimation model or risk factors. Previous researches aiming in this issue either excluded the CVDs population [ 16 , 17 ] or conducted in specific population with increased cardiovascular risk [ 15 , 18 ] or established CVDs [ 19 ]. Thus, it is not yet known whether their conclusions can be extrapolated to the general population.…”
Section: Introductionmentioning
confidence: 99%